MAP kinase pathway gene copy alterations in NRAS/BRAF wild-type advanced melanoma - Orouji, Elias; Orouji, Azadeh; Gaiser, Timo; Gebhardt, Christoffer; Utikal, Jochen (International journal of cancer, 2016)
Recent therapeutic advances have improved melanoma patientś clinical outcome. Novel therapeutics targeting BRAF, NRAS and cKit mutant melanomas are widely used in clinical practice. However therapeutic options in NRASwild-type/BRAFwild-type/cKitwild-type melanoma patients are limited. Our study shows that gene copy numbers of members of the MAPK signaling pathway vary in different melanoma subgroups. NRASwild-type/BRAFwild-type melanoma metastases are characterized by significant gains of MAP2K1 (MEK1) and MAPK3 (ERK1) gene loci. These additional gene copies could lead to an activation of the MAPK signaling pathway via a gene-dosage effect. Our results suggest that downstream analyses of the pMEK and pERK expression status in NRASwild-type/BRAFwild-type melanoma patients identify patients that could benefit from targeted therapies with MEK and ERK inhibitors.
Gesehen am 14.05.2019
Online 18 Dec 2015